Weaponized words : the strategic role of persuasion in violent radicalization and counter-radicalization - Braddock, Kurt 1981- (Cambridge University Press, 2020)
Strengthen your understanding of the persuasive mechanisms used by terrorist groups and how they are effective in order to defeat them. Weaponized Words applies existing theories of persuasion to domains unique to this digital era, such as social media, YouTube, websites, and message boards to name but a few. Terrorists deploy a range of communication methods and harness reliable communication theories to create strategic messages that persuade peaceful individuals to join their groups and engage in violence. While explaining how they accomplish this, the book lays out a blueprint for developing counter-messages perfectly designed to conquer such violent extremism and terrorism. Using this basis in persuasion theory, a socio-scientific approach is generated to fight terrorist propaganda and the damage it causes.